Mudharabah Deposit Returns in Islamic Banking: Pre IFSA Evidence from Malaysia. - Mohamed, Juliza; Nor, Norfadhzana Mohd; Azim, Zainal Azhar Zainal; Hussain, Hafezali Iqbal; Jaafar, Mohd Ezanni (International Journal of Engineering and Technology, 2018)
Mudharabah is a concept of joint venture between the investor (Rabbul Maal) and the entrepreneur (Mudharib) that would not exactly be involved in the business and at the end of a stipulated period, the entrepreneur would return to the investor the principal and the proportion of profits made. Return to the depositor will based on the Profit Sharing Ratio (PSR) and entrepreneur will be given return after deduction of Profit Earning Ratio (PER) and Internal rate of Return (IRR). This research analyzes the factor that contributes to the Rate of Return (ROR) given, whether it is influenced by Islamic Bank performance [Return on Asset (ROA), Return on Equity (ROE), Per Policy, Ownership or economic factors (GDP, UER). Data was collected from 16 Islamic banks in Malaysia from 2008-2013 (before IFSA 2013) The data was analyzed by using Stata software, and came out with Pool OLS, Panel OLS, Fixed Effect and Random Effect analysis that contributed to the finding of the study.